2013
DOI: 10.1016/j.elspec.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron spectroscopy and modeling of interface properties related to organic photovoltaic cells

Abstract: In this short review, we will give examples on how photoelectron spectroscopy (PES) assisted by models on interface energetics can be used to study properties important to bulk heterojunction type organic photovoltaic devices focusing on the well-known bulk heterojunction blend of poly(3-hexylthiophene):[6,6]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) and its model system P3HT:C 60 . We also will discuss some of the limitations of PES as applied to organic semiconductors (OS) and photovoltaic devices and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 63 publications
1
41
0
1
Order By: Relevance
“…[28][29][30][31][32] Previous work has demonstrated that the photovoltaic performance is sensitive to the surface electronic structure of cathode interlayer in terms of aligning energy levels at the interface with the bulk heterojunction layer. 33 [36][37][38][39] , whereas the IP of 7.75 ± 0.05 eV is high enough to block hole extraction at the donor polymer/ZnONP interface. 42 and ~ average for the series of formulations studies (see Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32] Previous work has demonstrated that the photovoltaic performance is sensitive to the surface electronic structure of cathode interlayer in terms of aligning energy levels at the interface with the bulk heterojunction layer. 33 [36][37][38][39] , whereas the IP of 7.75 ± 0.05 eV is high enough to block hole extraction at the donor polymer/ZnONP interface. 42 and ~ average for the series of formulations studies (see Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they do not have the same energy as bulk polarons, mainly due to Coulombic interaction with the opposite charge across the interface and variations in molecular order. Several different approaches have recently been developed to quantitatively treat the effects of screening and molecular order on the E ICT+,-energies in the ICT model [30][31][32][33][34][35] , and the abruptness of the integer charge transfer region also is being intensively researched and may be material dependent, as Neher and coworkers show a region extending beyond 50 nm for two types of polymers [18] whereas Frisch and coworkers found that the integer charge transfer only involved the first monolayer for rr-P3HT. [36] Here, the aim of our study is to explore the formation mechanism of the molecule-doped conjugated polymer/electrode interface by photoemission spectroscopy, and conclusively establish its universal energy level alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Ett sådant beteende förväntas hålla i allmänhet för låga till medelhögt [10][11][12] . In fact, even charge transport can be seen as a special injection behavior across organic-organic junction since the charges are localized on molecules 13 . Therefore, one of the crucial issues for organic electronic technologies is to understand and predict interface energetics and its effect on device operational efficiency [14][15][16] .…”
Section: Populärvetenskaplig Sammanfattningmentioning
confidence: 99%